The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/ijms232113233
|View full text |Cite
|
Sign up to set email alerts
|

Histomorphometry Changes and Decreased Reactivity to Angiotensin II in the Ileum and Colon of Streptozotocin-Induced Diabetic Rats

Abstract: Diabetes mellitus (DM) is a chronic progressive metabolic disorder associated with several gastrointestinal complications, affecting up to 75% of patients. Knowing that Angiotensin II (AngII) also regulates intestinal contraction, we decided to evaluate changes in ileum and colon histomorphometry and AngII reactivity in a rat model of DM. Streptozotocin (STZ, 55 mg/kg) was administered to induce DM to 24 adult male Wistar rats. Diabetic rats displayed all the characteristic signs of type 1 DM (T1DM) and fecal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 55 publications
(84 reference statements)
0
6
0
Order By: Relevance
“…Thus, the neuron alteration in the muscular plexus may explain the sensory-motor function changes. Intestinal function alteration in the strepto zotocin-induced diabetic rat is also associated with a declined level of Angiotensin II, which controls small intestine contraction [4]. Necrotic features of neurons in the Meissner plexus were lesser than degenerated form in the T2DM group (Figure 1-3: F) and may be addressed to neuro degenerative complications in the diabetic patient [24].…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Thus, the neuron alteration in the muscular plexus may explain the sensory-motor function changes. Intestinal function alteration in the strepto zotocin-induced diabetic rat is also associated with a declined level of Angiotensin II, which controls small intestine contraction [4]. Necrotic features of neurons in the Meissner plexus were lesser than degenerated form in the T2DM group (Figure 1-3: F) and may be addressed to neuro degenerative complications in the diabetic patient [24].…”
Section: Discussionmentioning
confidence: 95%
“…Histological alteration in the Auerbach plexus correlates to their function in controlling muscular contraction and intestine motility. It also may be associated with most cases in T2DM patients that manifest, abdominal pain, bloating, constipation, or diarrhea [4,5]. Damaged ENS by prolonged hyperglicemia and oxidative stress in T2DM denotes diabetes-associatedintestinal motility alteration [6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been demonstrated that the histomorphological and biomechanical remodeling of gastrointestinal tract including small intestine and colon occurred during the development of diabetes in several diabetic animals [ 2 ]. In STZ-induced diabetic rat models, both small intestine [ 15 , [18] , [19] , [20] , 36 ] and colon [ 14 , 20 , 21 , 36 ] expressed as increasing in wet weight per unit length, total wall and layered wall thickness, and wall area. Collagen increasing in colonic mucosa has been reported [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…SD rats aged 8 weeks were purchased from experimental Animal Center of Chongqing Medical University. The streptozotocin had toxic effects on pancreatic islet β-cells specially, causing almost all pancreatic β-cell necrosis [ 36 ]. Then STZ was dissolved into a sodium citrate buffer (50 mM, pH = 4.5) at a final concentration of 100 mg/mL.…”
Section: Methodsmentioning
confidence: 99%